Aplicação de princípios e parâmetros da teoria da gramática ao estudo do fenômeno de code-switching - Ribeiro, Ilza (DELTA: Documentação e Estudos em Linguística Teórica e Aplicada, 2019)
This paper deals with the code-switching phenomenon. Our main proposal is to demonstrate that the Theory of Grammar, as proposed by Chomsky (1981) and related works, can explain the way that code-switching works. The comparative research we present here reveals interesting facts about the possibilities of code-switching in pronominal subject constructions, in Wh- interrogatives, in negative clauses and unnaccusative structures. It empirically supports our hypothesis that the restrictions on switching have a wider domain and must be defined in terms of abstract mental representations. We admit that the investigation of the behavior of code-switching structures may provide clues elements to a better understanding of the human faculty of language.